Japhetic grammatology - Matthew Carson Allen (Interventions (London, England), 2022)
Nikolai Marr has attracted scholarly attention, but largely in a cautionary manner. His work is read as an ideological incursion into the science of language. More charitable assessments contextualize him within oriental studies in the Russian Empire and, in turn, early Soviet nationality policy. Yet ever since his fall from official favour in 1950, scholars have been reluctant to assess his scholarly contributions on their own merit. This essay is an attempt to reconsider Marr by historicizing the mainstream school of thought against which he is compared and found wanting. The pivotal figure for linguistics as we know it today was Ferdinand de Saussure, whose rigorous separation of the systematic synchronic moment of language from its protean historical existence solved a problem which had confounded his contemporaries. It made it possible to treat language as systematic from moment to moment, despite being subject to unforeseeable factors when viewed through time. In drawing this distinction Saussure fatefully privileged speech over writing as the truest instantiation of language. This allowed existing scientific-racist assumptions about the determining influence of anatomy on speech to remain unchallenged. Marr’s early career paralleled that of Saussure’s, yet when it came to the philosophy of language he started from very different premises. Marr identified the origin of language with gesture and tool use. His understanding of evolution departed radically from the organicism common to his contemporaries. Marr’s empirical statements about language are fanciful and cannot easily be recuperated. However, his work represents a tantalizing path not taken in the history of linguistics. As such it is worth reading Marr in the light of Derrida’s reading of Saussure. By bringing Marr into dialogue with better-known thinkers, and historicizing Derrida’s inaugural act of deconstruction, we can sketch the contours of a counter-tradition in linguistics.